Enterocytozoon bieneusi (Microsporidia): Identification of novel genotypes and evidence of transmission between sympatric wild boars (Sus scrofa ferus) and Iberian pigs (Sus scrofa domesticus) in Southern Spain. Issue 6 (15th June 2020) - Dashti, Alejandro; Rivero‐Juarez, Antonio; Santín, Mónica; López‐López, Pedro; Caballero‐Gómez, Javier; Frías‐Casas, Mario; Köster, Pamela C.; Bailo, Begoña; Calero‐Bernal, Rafael; Briz, Verónica; Carmena, David
Abstract: Microsporidia is a phylum of obligate emergent intracellular protist‐like fungi pathogens that infect a broad range of hosts including vertebrates and invertebrates. Enterocytozoon bieneusi is the most common cause of microsporidiosis in humans, affecting primarily immunosuppressed patients but also reported in immunocompetent individuals. Epidemiological information on the presence and molecular diversity of E. bieneusi in livestock and wildlife in Spain is limited. Therefore, the occurrence of this microsporidia was investigated in sympatric extensively reared Iberian pigs ( n = 186) and free ranging wild boars ( n = 142) in the province of Córdoba, Southern Spain. Forty‐two Iberian pigs (22.6%) and three wild boars (2.1%) were found E. bieneusi positive by PCR. In Iberian pigs, occurrence of E. bieneusi was significantly higher in sows than in fattening pigs (31.6% vs. 11.4%; p = .001). Five genotypes were identified in Iberian pigs, four previously reported (EbpA, PigEb4, O, Pig HN‐II) and a novel genotype (named PigSpEb1), while only two genotypes were identified in wild boars, EbpA and novel genotype PigSpEb1. All five genotypes identified belong to Group 1 suggesting zoonotic potential. This study constitutes the first report on the occurrence and molecular characterization of E. bieneusi in Iberian pigs and wild boars. The identification of two genotypes with zoonotic potential in sympatric Iberian pigs and wild boars suggests that E. bieneusi can be potentially transmitted between those two hosts, but also implies that they may act as natural sources of microsporidia infection to other hosts including humans.